Developing Speaking Skill of Grade X Students Through Dubbing Video at Senior High School - Faizah Putri; Jamiluddin Jamiluddin; Mashuri Mashuri; Mawardin M. Said (Universitas Islam Negeri Palopo, 2025)
This research aimed to prove whether the use of dubbing video can develop the speaking skills of the tenth-grade students of Senior High School. This research used a pre-experimental research design with a sample of 34 students selected using a purposive sampling technique. Purposive sampling technique was chosen because it focuses on students who have below average speaking skills. The class selected was class X B. Furthermore, research data were collected through speaking test administered twice as pre-test and post-test. The pre-test was administered to the experimental group before the treatment while the post-test was administered after the treatment. The researcher collected and analyzed data using the SPSS 29. The mean score of the pre-test is 29.53. Then, the mean scores of the post-test is 61.12. The data was statistically analyzed using the t-statistic formula with degrees of freedom (df) = N - 1 = 34 - 1 = 33. The result of this research showed the probability was 0.000 < 0.05. Based on this fact can be concluded that H0 was rejected. By looking at the result, it means that dubbing video was effective to improve students’ speaking skill.